FULFILLMENT OF FUNDAMENTAL RIGHTS FOR CHILD VICTIMS OF CRIMINAL ACTS AGAINST MORALITY - Fransiska Novita Eleanora; Lusia Sulastri (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Children as victims of sexual violence certainly feel the suffering they experience and the suffering as a result of the violence they experience as victims who are very vulnerable to violence and do not dare to put up the slightest resistance due to actions in the form of threats and even terror to victims and the perpetrators mostly come from close relatives who are supposed to provide protection to their children but instead become child predators. So children need to get legal protection In addition to imposing sanctions on perpetrators by imposing severe penalties on perpetrators, this means that if there is more than one victim, very severe penalties for perpetrators can be given, including life imprisonment. Apart from that, it also provides legal assistance in the form of rehabilitation both medically and socially as well as recovery of children so that they return to their original condition, especially in psychosocial terms, in returning their mental state and self-esteem to a more favorable state. Good. In addition, there is compensation that is charged to the perpetrator while the child is undergoing a period of care and treatment until he recovers because it is a form of child protection in providing mental, psychological and psychological recovery so that in the future the child can organize his life better towards his future.